Analysis of drug resistance of extended-spectrum beta-lactamases-producing Escherichia coli and Klebsiella pneumoniae in children with urinary tract infection - Keshi, Lu (Saudi Med J, 2019)
OBJECTIVES: To investigate the drug resistance of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli (E. coli) and Klebsiella pneumoniae (K.pneumoniae) in children with urinary tract infection (UTI) and to provide the rationale for clinical use of antibiotics. METHODS: This is a retrospective analysis of drug susceptibility in children with E. coli or K. pneumoniae-positive urine culture between August 2013 and August 2017, Shenzhen Children’s Hospital, Shenzhen, China. Drug resistance was statistically assessed using Fisher exact test and χ(2) test. RESULTS: A total of 698 cases of E. coli, 426 of which were confirmed ESBL-producing strains, and 217 cases of K. pneumoniae, including 111 ESBL-producing strains, were detected, and the difference in proportion of positive ESBL-producing strains (61.03% versus 51.15%) was statistically significant (p=0.010). The average drug resistance rates of E. coli and K. pneumoniae to piperacillin/tazobactam, meropenem, ertapenem, imipenem, and amikacin were <15%. The average resistance rates of ESBL-producing E. coli and K. pneumoniae to cefpodoxime, cefixime, cefazolin, and ceftriaxone was >98%, while average resistance rates for non-ESBL-producing bacteria to the above 4 drugs was <20%. CONCLUSION: In southern China, the proportion of ESBL-producing strains and the drug resistance rates of E. coli and K. pneumoniae in UTI in children was high, but their resistance rates to carbapenems and β-lactamase inhibitor complexes containing tazobactam were low. Carbapenems are the most effective antibacterial drugs for the treatment of ESBL-producing bacteria.